STATUS PERKEMBANGAN TERHADAP PERKEMBANGAN EMOSI ANAK DI KOTA SAMARINDA - Zulaikha, Fatma; Sureskiarti, Enok (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2018)
Child development can be viewed from various aspect such as physical, mental, socialand emotional. Emotional development is an important aspect in the pre school childdevelopment. This research aims to analyze the corellation between the childrendevelopment status and children emotional development with aged 36-72 months inSamarinda city. this research used anaylitical method with cross sectional approach. Therespondent of this research were 138 children aged 36-72 months in Samarinda, using purposivesampling with instrument in the form of observation sheet of KPSP and KMME. Research showedthat majority of children were in developmental stage according to age 81.0% and have normalemotional development of 84.8%. The result of the analysis showed the value of corellationcoefficient of 0.204 with significance value (2- tailed) of 0.017 > 0.05. This means that there wasa weak corellation between the child's developmental status with the emotional development ofchildren aged 36-72 months in Samarinda City.